Superparamagnetic iron oxide nanoparticles combined with NGF and quercetin promote neuronal branching morphogenesis of PC12 cells - Katebi, Samira (Int J Nanomedicine, 2019)
BACKGROUND: The investigation of agents promoting recovery of nerve regeneration following neurodegenerative diseases has been the most important issue in neuroscience. Nerve growth factor (NGF) and quercetin as potential flavonoids could possibly have therapeutic applications in the field of degenerative diseases such as Parkinson and Alzheimer. MATERIALS AND METHODS: The MTT assay was done at 24, 48, and 72 hours to examine the cytotoxicity of superparamagnetic iron oxide nanoparticles (SPIONs) and quercetin. We combined NGF and quercetin with different concentrations of SPIONs as novel compounds to study their effect on neuronal branching morphogenesis of PC12 cells. RESULTS: Morphological analysis showed a significant growth (P<0.001) in neurite length when PC12 cells were incubated in quercetin solution. We found a significant neurite outgrowth promotion and an increase in the complexity of the neuronal branching trees after exposing PC12 cells to both quercetin and SPIONs. In addition, a higher level of β3-tubulin expression was observed in these cells when treated with both quercetin and SPIONs. CONCLUSION: Different photographic analyses indicated that iron oxide nanoparticles function as an important factor in order to improve the efficiency of NGF through improving cell viability, cell attachment, and neurite outgrowth in the shelter of quercetin as an accelerator of these phenomena. The use of the quercetin–SPION complex as a suitable method for improving NGF efficacy and activity opens a novel window for substantial neuronal repair therapeutics.